Cavalrymen, Dowries, and Greek Onomastics: Two Oxyrhynchite Marriages - Winkler, Andreas (Zeitschrift für ägyptische Sprache und Altertumskunde, 2025)
Ptolemaic and Roman Oxyrhynchus is relatively well-documented through the Greek papyri from the site, while there are far fewer texts written in Egyptian from the same locality, which can offer additional perspectives. This paper takes a small step towards addressing this issue by presenting an edition and study of three Oxyrhynchite Demotic documents related to two marriages from the late 1 st century BC. Two papyri detail the first marriage, and the third text records the second one. Unique among Demotic materials published so far is the fact that one of the deeds is a ‘dowry document’ ( sẖ-n-grg.t ), providing new insights into the economic arrangements of Egyptian matrimony. The documents also contribute to our understanding of the relationship between military ranks, ethnicity, and onomastics at the time. The men bear Greek names and are, at least in one case, part of the catoecic cavalry at Oxyrhynchus, but still chose to enter the agreement through an Egyptian document. It is argued that while it is possible that the contracting parties may have been Hellenised Egyptians, it cannot be excluded that they were descendants of earlier Greek settlers who both spoke Egyptian and conducted their business in the native language.